Perception towards Online Education among the Secondary Level Students during COVID-19 Pandemic - Singh, Ajanta; Ranjitkar, U.D. (DMC Research Journal, 2023)
Online education is a type of educational instruction that is delivered through internet to students using their home computers. Since 2019 the effect of information technology on human life is immense and its role in education too cannot be subsided. The spread of COVID-19 led the closure of all educational institutions and has initiated online learning.We all are in the battlefield of COVID-19 Pandemic and our schools have been closed, despite of this crisis situation, we are trying to continue our academic journey and are involved in online education.This study aims to find out the perception of students towards online education.